Mono-/Bis-Alkenoic Acid Derivatives From an Endophytic Fungus Scopulariopsis candelabrum and Their Antifungal Activity - Tang, Jun; Huang, Xueshuang; Cao, Ming-Hang; Wang, Zhiyan; Yu, Zhiyin; Yan, Yijun; Huang, Jian-Ping; Wang, Li; Huang, Sheng-Xiong (Frontiers in Chemistry, 2022)
Guiding by an antifungal screening, seven mono-/bis-alkenoic acid derivatives (1‒7) were isolated from an endophytic fungi Scopulariopsis candelabrum. Their chemical structures were identified by 1H-NMR, 13C-NMR, 2D NMR and high-resolution mass spectrometry, as well as comparisons with previously reported literatures. Among them, fusariumesters C-F (2‒5) are bis-alkenoic acid derivatives dimerized by an ester bond, while acetylfusaridioic acid A (6) and fusaridioic acid D (7) are alkenoic acid monomers. All the isolates were submitted to an antifungal assay against Candida albicans. Resultly, compound 1 decorating with β-lactone ring turned out to be active with a MIC value of 20 μg/mL.